Comparison of frequency of low APGAR score in babies born to normotensive patients with and without hyperuricemia in a tertiary care hospital - Faryal Noman, Nusrat Noor; Rabiah Anwar, Rabiya Akbar; Khan Muhammad Yaqub (Journal of Rawalpindi Medical College, 2021)
Objective: To compare the frequency of low APGAR scores in babies born to normotensive patients with asymptomatic hyperuricemia with those without hyperuricemia. Study Design: Cohort Study. Place and Duration: This study was conducted at the department of gynaecology/obstetrics, Liaquat National Hospital Karachi from January 2015 to January 2016. Materials and Methods: The sample size was calculated by using openepic.com version 2, an open-source calculator. The sample size was calculated to be 165 in each group, which made a total of 330 patients. Non-probability consecutive sampling was chosen as the sampling technique. All normotensive pregnant females with blood pressure of less than 130/90 between 18 to 40 years of age, with singleton pregnancy at 37 weeks and beyond were included in the study. Normotensive pregnant females with hyperuricemia were the exposed group while normotensive pregnant females with normal uric acid levels were the non-exposed group. The exclusion criteria included patients with multiple gestations, medical disorders like gout, chronic renal failure, APLS, Rheumatoid Arthritis, etc, on anti-hypertensives and smokers. Fetal outcomes were assessed in all patients after delivery and a comparison of outcomes was made between two groups. Results: The study was designed to compare the frequencies of low APGAR scores in babies born to normotensive patients with asymptomatic hyperuricemia to those without hyperuricemia. The main outcome in group A i.e. exposed group was 29 babies with low APGAR score (<7) with 17.5% and in group B, which was non-exposed, 12 (7.57%) of babies had low APGAR score (<7). P-value came out to be 0.0010. The difference was statistically significant. Conclusion: It is concluded that there is a significant difference between the frequency of low APGAR scores in babies born to normotensive patients with hyperuricemia to those without hyperuricemia.